Pengaruh Kepercayaan, Komitmen dan Syariah Compliance terhadap Loyalitas Nasabah Pembiayaan Multijasa dengan Akad Ijarah di PT BPRS HIK Parahyangan Bandung - Ilev Ilev Latifah; Ida Rapida; Mimin Mintarsih (Ma'soem University, 2022)
Based on result of observations, that the background of this research is the number of multiservice financing customers with ijarah contracts that fluctuate, where there are many factors that influence the development of the number of multiservice financing customers with ijarah contracts at PT BPRS HIK Parahyangan Bandung. This study aims to determine how the influence of trust, commitment and sharia compliance on the loyalty of multi-service financing customers with ijarah contracts either partially or simultaneously at PT BPRS HIK Parahyangan Bandung. The object of research is multi-service financing customers with ijarah contracts at PT BPRS HIK Parahyangan Bandung. The type of research is associative quantitative, primary data and data collection techniques in the form of observation, interviews, literature study and questionnaires. Sampling with saturated sampling as many as 21 people. The results showed that there was an effect of trust on customer loyalty as seen from the analysis of the coefficient of determination of 40,3%, the effect of commitment on customer loyalty of 59,1% and the influence of sharia compliance on customer loyalty of 60,9%. There is a simultaneous influence between trust, commitment and sharia compliance on the loyalty of multiservice financing customers with ijarah contracts at PT BPRS HIK Parahyangan Bandung seen from the results of the coefficient of determination analysis with an R square value of 74,5%.